ECG findings in professional rugby players using international screening recommendations - Fiona Wilson; Karen Hind; Nicol van Dyk; Meagan Wasfy; Bradley Petek; Sarah Gustus; Clíodhna McHugh; Aubrey J Grant (BMJ Open Sport & Exercise Medicine, 2024)
Background While World Rugby guidelines do not mandate the inclusion of an electrocardiogram (ECG) for all players, this is required for entry into international rugby competitions. We, therefore, sought to describe sport-specific normative ECG values and evaluate the performance of contemporary athlete ECG guidelines in male and female professional rugby players.Methods We retrospectively analysed professional rugby players’ ECGs (n=356, male 79%) obtained during preparticipation screening (2010–2022), comparing by sex and playing position (forwards vs backs). ECGs were categorised as normal ‘training-related’, borderline and abnormal findings, as defined by the 2017 International Recommendations.Results 84% of players had one or more normal, ‘training-related’ findings, with males having a higher prevalence than females (91% vs 60%, p<0.001). Most ECG findings did not vary by position. No female player had borderline or abnormal ECG findings. Borderline findings were present in 3% (n=12/356) of players. Abnormal findings were present in 2% (n=7/356) of players. Overall, 2.2% of ECGs were ‘positive’ (n=8/356, including n=1 ECG with two borderline findings).Conclusions The application of contemporary ECG interpretation criteria resulted in a low positivity rate isolated to male players. These results help inform the logistic feasibility of ECG-inclusive screening, which is already required to enter major tournaments.